1999
DOI: 10.1021/jp991662h
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies of Metal Cation−Pyridine Complexes Containing Cu and Ag

Abstract: Photodissociative experiments were performed on Cu+−C5H5N and Ag+−C5H5N complexes in the gas phase. The dissociative ligand-to-metal charge-transfer fragments, pyridine+, were observed for both complexes. Photodissociation spectra were recorded as a function of laser wavelength. Two continuous, structureless bands were investigated in each complex. Because of the low-energy 2D state of the Cu atom, the Cu+−pyridine dissociative process is more complicated. Several possible mechanisms for this process have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 27 publications
4
52
2
Order By: Relevance
“…[90] These values are in fact slightly lower than the reliable experimental value of (204 AE 16) kJ mol À1 determined by mass spectrometry monitoring equilibria of ion-molecule reactions. [64,90] Interestingly, the Ag + ÀPy(p) isomer was not identified as a local minimum in previous calculations for Ag + ÀPy [62] and the related Cu + ÀPy dimer. [91] However, calculations for Au + ÀPy yielded a shallow local Au + ÀPy(p) minimum at the MP2/6-31G(d,p) level, [33] similar to the one obtained herein for Ag + ÀPy at the MP2 and B3LYP levels (Figure 1 c) ÀPy 2 isomer in the IRMPD spectrum.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…[90] These values are in fact slightly lower than the reliable experimental value of (204 AE 16) kJ mol À1 determined by mass spectrometry monitoring equilibria of ion-molecule reactions. [64,90] Interestingly, the Ag + ÀPy(p) isomer was not identified as a local minimum in previous calculations for Ag + ÀPy [62] and the related Cu + ÀPy dimer. [91] However, calculations for Au + ÀPy yielded a shallow local Au + ÀPy(p) minimum at the MP2/6-31G(d,p) level, [33] similar to the one obtained herein for Ag + ÀPy at the MP2 and B3LYP levels (Figure 1 c) ÀPy 2 isomer in the IRMPD spectrum.…”
mentioning
confidence: 79%
“…[60,61] Thus, it may be expected that the isolated Ag + ÀPy 2 complex adopts a linear PyÀAg + ÀPy configuration. Isolated complexes of metal ions with Py have been the subject of quantum chemical studies, [33,36,37,62] mass spectrometry, [35,63,64] and electronic spectroscopy. [33,36,62,65,66] Interestingly, mass spectra of Ag + ÀPy n clusters generated by laser ablation in a supersonic expansion do not show any magic numbers according to the expected strong preference for the formation of Ag + ÀPy 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantum-chemical investigation [106] of the supramolecular complexes (DPyEt) n (AgNO 3 ) m showed that one silver atom coordinates four ligands, and the attachment of a second atom provides an additional energy gain. Yang et al [107] established that the reversibility of binding in response to variations of the parameters of medium is more typical of silver than of copper, which is related to the fact that the binding energy in the latter case is almost one and a half times greater than that in the former one: 45.2 kcal versus 65.5 kcal.…”
mentioning
confidence: 99%